Microglia Contribution to the Regulation of the Retinal and Choroidal Vasculature in Age-Related Macular Degeneration - Alves, C..H. (2020)
The retina is a highly metabolically active tissue with high-level consumption of nutrientsand oxygen. This high metabolic demand requires a properly developed and maintained vascularsystem. The retina is nourished by two systems: the central retinal artery that supplies the innerretina and the choriocapillaris that supplies the outer retina and retinal pigment epithelium (RPE).Pathological neovascularization, characterized by endothelial cell proliferation and new vesselformation, is a common hallmark in several retinal degenerative diseases, including age-relatedmacular degeneration (AMD). A limited number of studies have suggested that microglia, the residentimmune cells of the retina, have an important role not only in the pathology but also in the formationand physiology of the retinal vascular system. Here, we review the current knowledge on microglialinteraction with the retinal vascular system under physiological and pathological conditions. To do so,we first highlight the role of microglial cells in the formation and maintenance of the retinal vasculaturesystem. Thereafter, we discuss the molecular signaling mechanisms through which microglial cellscontribute to the alterations in retinal and choroidal vasculatures and to the neovascularizationin AMD.